Neuroprotective Drug Discovery From Phytochemicals and Metabolites for CNS Viral Infection: A Systems Biology Approach With Clinical and Imaging Validation - Bhattacharjee, Anindita; Purohit, Pratik; Roy, Prasun K. (Frontiers in Neuroscience, 2022)
Background: Recent studies have reported that pulmo-neurotropic viruses can cause systemic invasion leading to acute respiratory failure and neuroinfection. The tetracycline class of secondary metabolites of microorganisms are effective against several migrating neurotropic viral disorders, as Japanese-Encephalitis (JE), Severe-Acute-Respiratory-Syndrome Coronavirus-2 (SARS-CoV-2), Human-Immunodeficiency-Virus (HIV), and Simian-Immunodeficiency-Virus (SIV). Another microbial secondary metabolite, cephalosporin, can be used for anti-viral combination therapy. However, a substantial public health debacle is viral resistance to such antibiotics and thus one needs to explore the antiviral efficiency of other secondary metabolites, as phytochemicals. Hence, here we investigate phytochemicals like podophyllotoxin, chlorogenic acid, naringenin, and quercetin, for therapeutic efficiency in neurotropic viral infections. Methods: To investigate the possibility of afferent neural pathways of migrating viruses in man, MRI scanning was performed on human subjects, whereby the connections between cranial nerves and brain-stem/limbic-region were assessed by fiber-tractography. Moreover, human clinical-trial assessment (n=140, p=0.028) was done for formulating a quantitative model of antiviral pharmacological intervention. Furthermore, docking-studies were performed to identify the binding affinity of phytochemicals towards antiviral targets as (i) host receptor [Angiotensin-converting Enzyme-2], (ii) main protease of SARS-CoV-2 virus (iii) NS3-Helicase/Nucleoside triphosphatase of Japanese-encephalitis-virus, and the affinities were compared to standard tetracycline and cephalosporin antibiotics. Then, network pharmacology analysis was utilized to identify the possible mechanism of action of those phytochemicals. Results: Human MRI-tractography analysis showed fiber connectivity, as (a) Path-1: From olfactory nerve to the limbic region (2) Path-2: From peripheral glossopharyngeal nerve and vagus nerves to midbrain-respiratory-center. Docking-studies revealed comparable binding affinity of phytochemicals, tetracycline, and cephalosporin antibiotics towards both (a) virus receptors, (b) host-cell receptors where virus-receptor binds. The phytochemicals effectively countered the cytokine storm-induced neuroinflammation, a critical pathogenic pathway. We also found that a systems-biology based double-hit mathematical bi-exponential model accounts for patient survival-curve under antiviral treatment, thus furnishing a quantitative-clinical-framework of secondary metabolite action on virus and host cells. Conclusion: Due to the current viral resistance to antibiotics, we identified novel phytochemicals that can have clinical therapeutic application to neurotropic virus infection. Based on human MRI-scanning and clinical-trial analysis, we demarcated the anatomical pathway and systems-biology-based quantitative formulation of the mechanism of antiviral action.